Introduction to the Thematic featuree: Partnership approaches to innovation driven by recent ICT developments: From local to global - Sahut, Jean-Michel; Braune, Eric; Dana, Léo-Paul (Management international / International Management / Gestiòn Internacional, 2024)
This special issue looks at partnership approaches to innovation thanks to recent developments in ICT, which enable the acquisition and transfer of skills, thus changing the processes and organization of firms. It is therefore essential to understand how ICT is used to establish internal and external collaborations for innovation. For this reason, we first examine the ICT used for innovation collaborations and how they contribute to the innovation process. The five articles then examine the effectiveness of ICT in three internal collaborations and two innovation partnerships. Finally, we propose a number of avenues for further research to better understand how ICTs and their use modify the way innovation takes place and the underlying organizational processes.